Tingkat Pelayanan (Level of Service) di Simpang Ruwet Kabupaten Jepara - Yayan Adi Saputro (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
Simpang Ruwet Roundabout in Jepara City is a form of traffic engineering to serve road users from General Sudirman, Ringin Raya, Cabbage. Sugiono, AR. Hakim, and HOS. Cokroaminoto roads. The meeting of vehicles with a heavy traffic flow creates a traffic jam at certain times for all directions. This study aims to determine the level of service at the Simpang Ruwet Roundabout in Jepara City, hence, it can provide an evaluation to determine the appropriate policy. Data were gathered from field surveys, including geometric conditions and average daily traffic (LHR). The data was processed based on the 1997 Indonesian Road Capacity Manual (MKJI) to obtain the capacity of each road and the level of road service. The results of the analysis showed the capacity at the roundabout for North West udder, North East udder, South East udder, and South West udder were 2894.98 smp/hour, 2901.87 smp/hour, 2887.59 smp/hour, and 2890.88 smp/hour, respectively. The Level of Service value was 0.45 which is a B category.